COVID-19 and the food system: Setback or opportunity for gender equality? - Ragasa, Catherine; Lambrecht, Isabel B. (International Society for Plant Pathology, 2020)
Agriculture and the food sector are critical to food and nutrition security because they not only produce food but also contribute to economic empowerment by employing a large share of female and male workers, especially in developing countries. Food systems at all levels―globally, domestically, locally, and in the home― are expected to be highly affected by the COVID-19 crisis. Women and men work as food producers, processors, and traders and will likely be impacted differently. Shocks or crises can exacerbate or reduce gender gaps, and so can policy responses to mitigate the impact of these crises or shocks. We offer some perspectives and available country examples on how the COVID-19 crisis and responses to the crisis could be a setback or offer opportunities for gender equality in the food system.